Acute pancreatitis - Štimac, Davor (Henry Stewart Talks, 2011)
Epidemiology and etiology, Pathophysiology of acute pancreatitis, Diagnostic methods, Revision of the Atlanta classification, Severity prediction, Outcomes of acute pancreatitis, Therapeutic options
Updated at 2017/08/31